PENGUATAN KAPASITAS EKONOMI SANTRI MELALUI INOVASI DAN KREATIVITAS KEWIRAUSAHAAN DI PESANTREN UMMUL QURO - Mahmudi Mahmudi; Enny Savitri; Reni Hindriari (Jurnal Pengabdian Tangerang Selatan [JURANTAS], 2026)
This Community Service (PKM) activity aims to strengthen the economic capacity of students through the development of innovation and entrepreneurial creativity at the Ummul Quro Islamic Boarding School, South Tangerang City. Pesantren as the oldest Islamic educational institution in Indonesia has great potential in producing young entrepreneurs with character, but still faces serious challenges in terms of business literacy, simple financial management, and competitive product development in the market. The implementation of PKM lasted for three days, namely from March 7 to 9, 2026, involving 60 active students, boarding school administrators, and a team of lecturers from the Management Study Program of Pamulang University. The methods used include interactive lectures, focused group discussions (FGDs), simulations of the preparation of Business Model Canvas, digital marketing workshops, and direct assistance in the development of local potential-based business ideas. The evaluation was carried out through pre-test and post-test, where the results showed an increase in the average score of entrepreneurial understanding by 85.7%, from 42 to 78 on a scale of 100. The participants managed to produce 10 business plans in the Business Model Canvas format that were considered feasible and relevant to the local potential of the Islamic boarding school. The institutional commitment of the leadership of the Ummul Quro Islamic Boarding School to integrate entrepreneurship materials into the formal curriculum of the Islamic boarding school is a strategic achievement that ensures the sustainability of the program's impact. This activity is expected to be a model of pesantren-based economic development that can be widely replicated in other Islamic educational institutions throughout Indonesia.